The fourth fundamental form of the torus hypersurface - Güler, Erhan (My University, 2020)
We introduce the fourth fundamental form of the torus hypersurface in the four dimensional Euclidean space. We also compute I, II, III and IV fundamental forms of a torus hypersurface.
Keywords: Four space; Torus hypersurface; Fourth fundamental form